2009
DOI: 10.1007/s11252-009-0081-3
|View full text |Cite
|
Sign up to set email alerts
|

Urban forest biomass estimates: is it important to use allometric relationships developed specifically for urban trees?

Abstract: Many studies have analyzed the benefits, costs, and carbon storage capacity associated with urban trees. These studies have been limited by a lack of research on urban tree biomass, such that estimates of carbon storage in urban systems have relied upon allometric relationships developed in traditional forests. As urbanization increases globally, it is becoming important to more accurately evaluate carbon dynamics in these systems. Our goal was to understand the variability and range of potential error associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
139
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(158 citation statements)
references
References 27 publications
2
139
0
4
Order By: Relevance
“…However, due to local regulations, liability, and public perceptions and safety, destructive sampling is expensive and difficult in an urban environment. Although McHale et al (2009) found that some of these allometric equations for forestgrown trees yield similar biomass estimates for urbangrown trees; these allometric equations can produce very different results when applied to sites outside the region where the equations were originally developed (ZapataCuartas et al 2012).…”
Section: Allometric Equations and Carbon Storagementioning
confidence: 99%
See 3 more Smart Citations
“…However, due to local regulations, liability, and public perceptions and safety, destructive sampling is expensive and difficult in an urban environment. Although McHale et al (2009) found that some of these allometric equations for forestgrown trees yield similar biomass estimates for urbangrown trees; these allometric equations can produce very different results when applied to sites outside the region where the equations were originally developed (ZapataCuartas et al 2012).…”
Section: Allometric Equations and Carbon Storagementioning
confidence: 99%
“…According to Jo and McPherson (1995), McHale et al (2009), andYoon et al (2013) the use of allometric biomass equations based on forest-grown trees can overestimate or underestimate urban tree biomass. For example an urban tree with the same DBH or height as a forest trees could have a different biomass due to the conditions of the urban environment relative to forest-grown trees (Jo & McPherson 1995).…”
Section: Model Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Also the variables that affect urban tree growth (i.e. soil, water, solar resources) are different among cities, therefore allometric relationships within those urban trees vary (McHale et al 2009). …”
Section: Introductionmentioning
confidence: 99%